Energetic and exergetic investigations of an innovative light-based hydrogen production reactor. (31st May 2018) - Acar, Canan; Dincer, Ibrahim
Abstract: In this study, it is aimed to thermodynamically study and experimentally test a continuous type hybrid photoelectrochemical hydrogen production system. The hybrid system considered in this study is capable of enhancing solar spectrum utilization via the combination of photocatalysis and PV/T. In addition, the system eliminates the electron donor requirement of photocatalysis by employing photoelectrodes. Which, as a result, risk of potentially harmful pollutant emissions is reduced. In this study, the present system is investigated in electrolysis operation under three different inlet mass flow rates (0.25, 0.50, and 0.75 g/s). The experimental results are compared to the thermodynamic model outputs. Parametric studies are conducted by changing the inlet mass flow rate from 0 to 1 g/s. The present experimental results suggest that the highest hydrogen production rate is observed at 0.75 g/s inlet mass flow rate, which is 2.43 mg/h. The highest energy and exergy efficiencies are calculated at 0.25 g/s, which are 36% and 32%, respectively. Furthermore, thermodynamic model outputs are confirmed to have a good agreement with the experimental results. Highlights: Experimental investigation and thermodynamic assessment of a hybrid PEC system are presented. The hybrid system is capable of producing H2, Cl2, and NaOH simultaneously. The system is tested experimentally at three inlet mass flow rates. The parametric studies are done by varying the inlet mass flow rate between 0 and 1 g/s. The optimum inlet mass flow rate is calculated.